The Effect of Perceived Big Data Marketing Capability on Consumer Loyalty: The Mediating Role of Personalized Customer Experience, Customer Trust, and Perceived Value and the Moderating Role of Privacy Concern - Yokie Radnan; Salamatun Asakdiyah; Sylvia Samuel (Global Research Collaboration, 2026)
This study analyzes the effect of Perceived Big Data Marketing Capability (PBDMC) on Consumer Loyalty by positioning Personalized Customer Experience, Customer Trust, and Perceived Value as serial mediating variables and Privacy Concern as a moderating variable. The study was conducted in Banten Province, Indonesia, involving 324 respondents who had interacted with data-driven digital marketing practices, such as personalized product recommendations, targeted advertising, search-history-based promotions, and digital services tailored to user preferences. This research employed a quantitative explanatory design. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings show that PBDMC positively influences Personalized Customer Experience and Consumer Loyalty. Personalized Customer Experience significantly enhances Customer Trust and Perceived Value, while Customer Trust positively affects Perceived Value and Consumer Loyalty. Perceived Value is also an important predictor of Consumer Loyalty. The moderation result indicates that Privacy Concern weakens the relationship between Personalized Customer Experience and Customer Trust. This means that data-driven personalization does not always generate trust when consumers perceive that their privacy is at risk. This study contributes theoretically by developing a serial mediation and moderation model within the data-driven marketing literature. Practically, the findings emphasize the importance of managing consumer data transparently, securely, ethically, and value-oriented so that data-based marketing practices can build sustainable Consumer Loyalty.